Pengaruh e-Wom dan Online Advertising dalam Membangun Brand Image Pada Produk HP Vivo - Wulan Sari; Lalu M. Furkan; Handry Sudiartha Athar (Postgraduate, University of Mataram, 2021)
The purpose of this study was to find out the influence of Brand Image on HP Vivo Products at the Faculty of Economics and Business of Mataram University and to find out the influence of Online Advertaising on Brand Image on HP Vivo Products at the Faculty of Economics and Business of Mataram University. This research is an associative research with a research approach using quantitative approaches. This research was conducted in the Faculty of Economics and Business of Mataram University. The data collection method used in this study is a sample survey. The population in this study was consumers who shopped for Vivo mobile products. A study sample of 98 respondents was determined by a non probability sampling technique, a purposive sampling method. Collecting the necessary data and information, the study used interview and questionnaire techniques. The data collection tool used in the study was a questionnaire. Data analysis techniques are performed using multiple linear regressions. The results showed that (1) variable e-wom had a significant influence on brand image and buying interest in vivo products in the city of Mataram; (2) Online Advertising variables have a positive and significant influence on the decision to purchase vivo products in the city of Mataram